2021
DOI: 10.1055/a-1673-5603
|View full text |Cite
|
Sign up to set email alerts
|

INOVASIA Study: A Randomized Open Controlled Trial to Evaluate Pravastatin to Prevent Preeclampsia and Its Effects on sFlt1/PlGF Levels

Abstract: Objectives To evaluate the effect of pravastatin to prevent preeclampsia (PE) in pregnant women at a high risk of developing preeclampsia and the maternal and perinatal outcomes and the sFlt1/PLGF ratio. Study Design This is an open labelled RCT part of INOVASIA trial. Pregnant women at a high risk of developing PE were recruited and randomized into an intervention group (40) and a control group (40). The inclusion criteria consisted of pregnant women with positive clinical risk factor and abnormal uterine art… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…In the Surabaya arm of the INOVASIA study we were able to show that the serum sFlt-1 levels rose significantly during gestation in the control group, but only slightly in the pravastatin group. Serum PlGF levels went down significantly in the control group, but only slightly (non significant) in the pravastatin group 30 . Mendoza et al also reported that the ratio of sFlt1/PlGF was lowered in women with early onset fetal growth restriction treated with pravastatin compared to no therapy 63 .…”
Section: Accepted Manuscriptmentioning
confidence: 79%
See 4 more Smart Citations
“…In the Surabaya arm of the INOVASIA study we were able to show that the serum sFlt-1 levels rose significantly during gestation in the control group, but only slightly in the pravastatin group. Serum PlGF levels went down significantly in the control group, but only slightly (non significant) in the pravastatin group 30 . Mendoza et al also reported that the ratio of sFlt1/PlGF was lowered in women with early onset fetal growth restriction treated with pravastatin compared to no therapy 63 .…”
Section: Accepted Manuscriptmentioning
confidence: 79%
“…24 We recently measured the serum levels of HO-1 and sFlt1 in early-onset preeclampsia, late-onset preeclampsia, and normal pregnancy. 25 There was no difference in serum HO-1 levels across the three groups, and no correlation between serum HO-1 and sFlt-1 levels. 25 Correcting the imbalance may eventually resolve the maternal endothelial cell dysfunction.…”
mentioning
confidence: 77%
See 3 more Smart Citations